PREDICTING MORTALITY OUTCOME IN NEONATES DIAGNOSED WITH HYPOXIC ISCHEMIC ENCEPHALOPATHY: A CROSS-SECTIONAL STUDY. (Student's Journal of Health Research Africa, 2023)
Objectives This study aimed to explore the relationship between varying HIE grades in newborns and levels of reduced glutathione and superoxide dismutase in cerebrospinal fluid, investigating their potential as predictive markers for mortality. The goal was to assess the utility of CSF-based free radical scavengers and antioxidants in predicting mortality in newborns with HIE. MethodsA 3-year cross-sectional study at Patna Medical Collage and Hospital in Patna, Bihar, India included 86 newborns with hypoxic ischemic encephalopathy. Standard treatments were administered, and CSF analysis for superoxide dismutase and reduced glutathione followed exclusion criteria. Results In the study of 140 neonates, 54 were excluded due to consent issues, leaving 86 examined by Sarnat staging. Cerebrospinal fluid superoxide dismutase significantly decreased with HIE severity (81.8, 53.2, 31.6 U/ml, P < 0.001). Reduced glutathione exhibited a negative correlation (1354.6, 1041.9, 692.7 ng/ml, P < 0.001). Deceased neonates showed significantly lower SOD (61.43 U/ml, P < 0.001) and GSH (22.45 U/ml, P < 0.001) compared to survivors (1104.32 ng/ml, 584.68 ng/ml, respectively). ConclusionThe current study reveals that diminished levels of reduced glutathione (GSH) and superoxide dismutase (SOD) in cerebrospinal fluid indicate the intensity of hypoxic ischemic encephalopathy (HIE) and correlate with newborn mortality, highlighting the critical role of oxidative stress. Establishing cut-off values for these antioxidants in CSF may serve as markers for HIE staging and prognosis, guiding the development of targeted neuroprotective therapies for neonates. Recommendation The study recommends conducting larger, prospective investigations to address limitations like the small sample size and retrospective design. Furthermore, exploring interventions targeting oxidative stress is advised to enhance outcomes in newborns with HIE.
Keywords: Birth Asphyxia; Hypoxic Ischemic Encephalopathy; Cerebrospinal Fluid